2017
DOI: 10.1016/j.ultrasmedbio.2017.08.1881
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Study of Acoustic Angiography in the Breast and Peripheral Vasculature

Abstract: Screening with mammography has been demonstrated to increase breast cancer survival rates by about 20%. However, the current system in which mammography is used to direct patients toward biopsy or surgical excision also results in relatively high rates of unnecessary biopsy, as 66.8% of biopsies are benign. A non-ionizing radiation imaging approach with increased specificity might reduce the rate of unnecessary biopsies. Quantifying the vascular characteristics within and surrounding lesions represents one pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…As ultrasound technologies continue to improve, these methods will become more widespread and accessible. For example, acoustic angiography that uses dual‐frequency ultrasound transducer technology to enhance spatial resolution and contrast‐to‐tissue ratio was recently used to visualize the microcirculation in the human breast 181 …”
Section: Ultrasound (Us) Imagingmentioning
confidence: 99%
“…As ultrasound technologies continue to improve, these methods will become more widespread and accessible. For example, acoustic angiography that uses dual‐frequency ultrasound transducer technology to enhance spatial resolution and contrast‐to‐tissue ratio was recently used to visualize the microcirculation in the human breast 181 …”
Section: Ultrasound (Us) Imagingmentioning
confidence: 99%
“…Using this technique, researchers have observed microvascular patterns which exhibit significant differences in both morphology and density of microvasculature, in both rat and mouse tumor models [14][15][16][17][18][19][20][21]. It was also recently demonstrated to be feasible for imaging microvasculature in humans, depicting breast vasculature as small as 200 μm to a depth of approximately 15 mm [22].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of receiving at several times the transmit frequency (as in the case of AA), subharmonic imaging receives at 1/2 the transmit frequency, and since microbubbles are most responsive near their resonance, around 1-6 MHz depending on the size and shell composition, sub-harmonic imaging suffers from very poor spatial resolution limiting its utility in preclinical applications. Due to the reliance of AA receiving high frequencies, good spatial resolution is achieved at the expense of poor depth of penetration into tissue, and thus the AA technique is likely limited to imaging preclinical animal models, or superficial clinical targets of a few cm (Shelton et al 2017). This is not the first study to implement AA to evaluate tumor response to therapy, as previous studies have shown both mouse and rat models responding to anti-angiogenic therapy (Rojas et al 2018), and broad beam radiation (Kasoji et al 2018).…”
Section: Introductionmentioning
confidence: 99%